Childhood asthma and household exposures to nitrogen dioxide and fine particles: a triple-crossover randomized intervention trial. (3rd April 2023) - Gent, Janneane F.; Holford, Theodore R.; Bracken, Michael B.; Plano, Julie M.; McKay, Lisa A.; Sorrentino, Keli M.; Koutrakis, Petros; Leaderer, Brian P.
Abstract: Objective: Triple-crossover randomized controlled intervention trial to test whether reduced exposure to household NO2 or fine particles results in reduced symptoms among children with persistent asthma. Methods: Children ( n = 126) aged 5–11 years with persistent asthma living in homes with gas stoves and levels of NO2 15 ppb or greater recruited in Connecticut and Massachusetts (2015–2019) participated in an intervention involving three air cleaners configured for: (1) NO2 reduction: sham particle filtration and real NO2 scrubbing; (2) particle filtration: HEPA filter and sham NO2 scrubbing; (3) control: sham particle filtration and sham NO2 scrubbing. Air cleaners were randomly assigned for 5-week treatment periods using a three-arm crossover design. Outcome was number of asthma symptom-days during final 14 days of treatment. Treatment effects were assessed using repeated measures, linear mixed models. Results: Measured NO2 was lower (by 4 ppb, p < .0001) for NO2 -reducing compared to control or particle-reducing treatments. NO2 -reducing treatment did not reduce asthma morbidity compared to control. In analysis controlling for measured NO2, there were 1.8 (95% CI −0.3 to 3.9, p = .10) fewer symptom days out of 14 in the particle-reducing treatment compared to control. Conclusions: It remains unknown if using an air cleaner alone can achieve levels of NO2 reduction large enough to observe reductions in asthma symptoms. We observed that in small, urban homes with gas stoves, modest reductions in asthma symptoms occurred using air cleaners that remove fine particles. An intervention targeting exposures to both NO2 and fine particles is complicated and further research is warranted. Registration Number: NCT02258893.